2010
DOI: 10.1097/mjt.0b013e3181e00bf1
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a): From Molecules to Therapeutics

Abstract: Lipoprotein (a) [Lp(a)] was discovered by Kare Berg in 1963 from the study of low-density lipoprotein genetic variants. Lp(a) contains a unique protein, apolipoprotein(a), which is linked to the Apo B-100 through a disulfide bond that gives it a great structural homology with plasminogen, and confers it atherogenic and atherothrombotic properties. Interest in Lp(a) has increased because an important association between high plasma levels of Lp(a) and coronary artery disease and cerebral vascular disorders has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 101 publications
0
14
0
1
Order By: Relevance
“…Based on these premises, dyslipidemia, and inflammation, Lp(a) plays an important role at the molecular level both for CVD and MS when its plasmatic concentration is elevated, being able to generate both of the aforementioned basic disturbances [31–33]. However, research assessing its epidemiological behavior remains scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these premises, dyslipidemia, and inflammation, Lp(a) plays an important role at the molecular level both for CVD and MS when its plasmatic concentration is elevated, being able to generate both of the aforementioned basic disturbances [31–33]. However, research assessing its epidemiological behavior remains scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated lipoprotein(a) levels are associated with an increased risk of atherosclerosis-related events such as cardiovascular disease and stroke. Lipoprotein(a) is believed to be involved in forming atherosclerotic plaques and enhancing platelet interaction [17]. It also correlates with inflammatory activity, as seen in patients with rheumatoid arthritis (RA) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Lipoprotein(a) [Lp(a)], first discovered by Kare Berg in 1963, is a low-density lipoprotein (LDL)-like particle containing apolipoprotein(a) [apo(a)] and apolipoprotein B-100 (apo-B100) linked through a disulfide bond [1]. It has been shown that Lp(a) contributes to atherosclerosis through accelerated transport of oxidized phospholipids [2] and inhibition of fibrinolysis [3].…”
Section: Introductionmentioning
confidence: 99%